STRATEGI PENGEMBANGAN USAHA MIKRO KECIL MENENGAH (UMKM) DI DAERAH TUASAN DALAM PERSPEKTIF EKONOMI ISLAM UNTUK MENINGKATKAN KESEJAHTERAAN PEDAGANG KAKI LIMA - Zainarti Zainarti; Chairun Nisa Panjaiatan; Ditia Azzahra Aswin Tanjung; Restu Agung Syahputra (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
This research aims to analyze MSME development strategies in the Tuasan area using an Islamic economic perspective to improve the welfare of street vendors. Apart from that, this research also aims to determine the strengths, weaknesses, opportunities and threats faced by MSMEs in the Tuasan area. This research uses a qualitative approach with a case study method to explore strategies for developing Micro, Small and Medium Enterprises (MSMEs) in the Tuasan area from an Islamic economic perspective, as well as their impact on the welfare of street vendors. A qualitative approach was chosen because it allows for an in-depth understanding of the local context and socio-economic dynamics that influence MSMEs and street vendors. The case study method is used because the focus of this research is on one specific community, namely street vendors in Tuasan, allowing a detailed description of the application of Islamic economic principles in the daily lives of street vendors. Based on the results of this research, MSMEs in the Tuasan area have significant strengths and opportunities to develop, although they are also faced with various weaknesses and threats. By applying Islamic economic principles, such as fairness in prices, use of capital based on profit sharing, improving product quality and innovation, as well as social and educational empowerment, MSMEs in Tuasan can improve the welfare of street vendors and make a positive contribution to society as a whole.